"Recovery of Kidney Function after 2 Years on Hemodialysis Due to Intra-renal Thrombotic Microangiopathy Induced by Interferon β-1a” - Al-Bader, Shaikha; El-Reshaid, Kamel (International Journal of Innovative Research in Medical Science, 2018)
Beta interferons (IFN) are the first approved and the most-widely used disease modifying therapies for relapsing-remitting multiple sclerosis. Despite their good overall long-term safety data they can rarely cause renal thrombotic microangiopathy (TM). In this report, we describe a patient who developed a rapidly progressive renal failure with hypertension after receiving IFN-β-1a for 2 years. She had just mild anemia without laboratory evidence of hemolysis and her peripheral platelets counts were normal. Kidney biopsy was done despite her relatively smaller-sized kidneys at 8.8 cm. It showed intra-renal acute on top of chronic TM. She did not have antiphospholipid antibodies, hypercoagulable state or genetic predisposition to TM. ADAMTS13 activity was normal. Despite discontinuation of IFN, plasma exchange and high dose corticosteroids for 2 weeks, she progressed fast to being dialysis-dependent. Her celiac and renal angiograms were normal. IFN β-1a was replaced with Azathioprine and her severe hypertension was controlled. Interestingly, she remained dialysis-dependent for 2 years and subsequently, had recovered. One year later, her serum creatinine is at 129 umol/L and her kidneys size is 8 cm. In-conclusion, IFN-β treatment can induce renal-limited TM which may recover up to 2 years later.